Un intérêt « sans mélange de peine » : Clarisse, Julie et l’optimum du roman épistolaire pathétique - Marilina Gianico (Etudes Epistémè)
In his famous comparison between God’s creation and the action of a novelist, Leibniz reminds us that the best of all possible worlds (real as well as fictional) is not a world released from evil, but a universe finding a balance between variety and coherence. The idea of optimum is then like a function representing the best relation between several parameters, as the most recent critical literature has shown. This article is grounded on these presuppositions and analyses how two 18th century novels, Richardson’s Clarissa and Rousseau’s Julie or the New Heloise, starting from a similar situation, deeply differ in their treatment of the problem of evil in the diegetic economy. The article proposes a study of the consequences of the theological conceptions of the authors on the narrative technique, on the relation with the reader and, finally, on the poetics of the two novels.